MiRNAs Identify Shared Pathways in Alzheimer's and Parkinson's Diseases. Issue 8 (August 2019) - Sadlon, Angélique; Takousis, Petros; Alexopoulos, Panagiotis; Evangelou, Evangelos; Prokopenko, Inga; Perneczky, Robert
Abstract : Despite the identification of several dozens of common genetic variants associated with Alzheimer's disease (AD) and Parkinson's disease (PD), most of the genetic risk remains uncharacterised. Therefore, it is important to understand the role of regulatory elements, such as miRNAs. Dysregulated miRNAs are implicated in AD and PD, with potential value in dissecting the shared pathophysiology between the two disorders. miRNAs relevant to both neurodegenerative diseases are related to axonal guidance, apoptosis, and inflammation, therefore, AD and PD likely arise from similar underlying biological pathway defects. Furthermore, pathways regulated by APP, L1CAM, and genes of the caspase family may represent promising therapeutic miRNA targets in AD and PD since they are targeted by dysregulated miRNAs in both disorders. Highlights: Systematic reviews and meta-analyses clearly identify sets of miRNAs that are dysregulated in AD and postmortem brain samples from patients with PD. Given the central role of miRNAs in neuronal function and the close link between select miRNAs and key pathological processes in AD and PD, it was proposed that this information could be used to better understand the shared pathobiology of the two disorders. It was suggested that miRNA changes are cell type specific and the shifting balance between different cell populations as neurodegeneration advances may be important when miRNAs are considered as diagnostic or therapeutic targets. Similar evidence in other disease areas, such as cancer, has successfully been applied to develop more effective strategies for early detection and disease-modifying interventions.